Studi Kasus: Regulasi Diri pada Ibu yang Memiliki Anak Usia Sekolah Dasar di SD AL-Hijriyah Selama Blended Learning - Agnes Yunitha Kristina; I Rai Hardika; Ni Nyoman Ari (Humanitas (Jurnal Psikologi), 2022)
This study aims to explain maternal self-regulation using Zimmerman's theory which consists of three aspects, namely metacognition, motivation, and behavior. This study uses mothers who have children of elementary school age and at Al-Hijriyah Elementary School as subjects in this study. This study uses a qualitative method with a case study approach. Using interviews, observations, and documentation as research data collection methods. The subjects in this study consisted of 3 subjects and 1 informant for each subject. The results of this study indicate that, self-regulation of mothers who have children at Al-Hijriyah Elementary School in a mixed manner, namely the presence and monitoring of children, self-control and actions in control as a mother, as well as the mother's ability to adjust and adapt to the safe situation of children learning in a blended way. Based on the research found to determine that the mother is able to self-regulate and it was found that the factors that influence the mother's regulation are internal factors (self).